Development of a Syphilis-Specific Molecular Assay. (9th November 2022) - Kwon, Regina; Lieberman, Nicole; Haynes, Austin; Penewit, Kelsi; Holmes, Elizabeth; Thompson, Joshua; Giacani, Lorenzo; Greninger, Alexander; Salipante, Stephen
Abstract: Syphilis is a sexually transmitted disease caused by the spirochete Treponema pallidum subspecies pallidum . Rates of infection have been rising for 20 years, with nearly 39, 000 cases of primary and secondary syphilis reported in the United States in 2019. Early diagnosis is critical for preventing disease progression and transmission but remains challenging. Dark-field microscopy is laborious and unavailable in most clinical laboratories. Serology, the mainstay of diagnosis and monitoring, may be nonreactive in up to 47% of patients with early primary syphilis. Immunofluorescence and immunohistochemistry can be difficult to interpret due to cross-reactivity and nonspecific staining. Given these limitations, nucleic acid amplification testing (NAAT) via polymerase chain reaction (PCR) is an attractive diagnostic tool. It offers the possibility of high sensitivity and specificity; detection across a wide variety of specimens; and applicability to early primary lesions, extragenital sites, and late-stage syphilis. However, no FDA-approved T. pallidum NAATs exist, and few commercial laboratory-developed tests are available. Due to this lack, clinicians have turned to broad-range bacterial PCR targeting the 16S rRNA gene offered by our molecular microbiology reference laboratory, particularly for detection in formalin-fixed paraffin-embedded tissue. To understand usage patterns, we searched the laboratory information system, revealing 45 specimens (representing 40 unique patients) in which T. pallidum was detected by this assay. We identified an additional 4 specimens from 2 patients in whom syphilis was suspected. The results of gold-standard testing were available for 19 cases, yielding a positive percent agreement of 73% and negative percent agreement of 100%. These findings both highlight the utility of a molecular assay and suggest an organism-specific assay could increase sensitivity. To build on the promise of PCR-based T. pallidum diagnostics, we developed an assay targeting tprCDFI, a 400bp region conserved across four paralogous genes and unique to T. pallidum . We hypothesized that the multiple copies of tprCDFI will increase the assay's analytical sensitivity as compared with the single-copy tp47 and two-copy 16S rRNA loci. Ten candidate primer pairs were evaluated bioinformatically for species-specificity and five were chosen for empiric testing. Two primer sets successfully detected both synthetic DNA target and gDNA extracted from two clinical isolates and two laboratory strains (Nichols, SS14) of T. pallidum. The analytes were spiked into 50ng of human gDNA to simulate patient matrix. Preliminary experiments showed a limit of detection of 40 or fewer genomes per reaction. Studies are under way to determine analytical sensitivity, specificity, and limit of detection and to compare the performance of the tprCDFI primers with those for 16S rRNA and tp47 genes before proceeding to clinical validation in a variety of pluri- and paucicellular specimens.